“Lure fishing” strategies by Mothocya parvostis (Isopoda: Cymothoidae): Feeding behavior-mediated infestation on juveniles of black sea bream, Acanthopagrus schlegelii - Hiroki Fujita; Kentaro Kawai; Michitaka Shimomura; Tetsuya Umino (International Journal for Parasitology: Parasites and Wildlife)
Cymothoidae Leach, 1818 (Isopoda) are parasitic crustaceans that infest fish inhabiting marine, brackish, and freshwater environments. Few studies have examined the strategies Cymothoidae use to parasitize their hosts. In this study, we tested the hypothesis that Mothocya parvostis Bruce, 1986 (Isopoda: Cymothoidae) parasitizes its hosts by exploiting its feeding behavior. In our infestation experiments, juveniles of the black sea bream Acanthopagrus schlegelii (Bleeker, 1854) were infested with M. parvostis mancae in water tanks with and without nauplii of Artemia Leach (1819) (A. schlegelii feed). Overall, 46 of 100 A. schlegelii juveniles were parasitized, 36 of which were parasitized when they attempted to consume the mancae. The presence of Artemia resulted in a significantly lower infestation prevalence and a longer time to infestation. This may be attributed to the presence of Artemia diverting the attention of A. schlegelii juveniles and reducing their feeding on mancae. Mothocya parvostis exploits the feeding behavior of its host to increase its infestation success, similar to “lure fishing,” which may help maintain its high prevalence in hosts.